Brazil : The New Growth Agenda, Volume 2. Detailed Report - World Bank (Washington, DC, 2013)
During the last century, Brazil was one of the fastest growing economies in the world. Between 1901 and 2000, Brazil's Gross Domestic Product (GDP) per capita grew at an average annual rate of 4.4 percent. Brazil's long-run growth has rivaled that of counties such as South Korea, universally praised as a stellar performer. Brazil does not received the same praise. Perhaps one reason is that more has been expected of Brazil, especially by Brazilians themselves. After all the country is richly endowed with natural resources and is blessed with an energetic people. Perhaps is that economic growth in Brazil has been more erratic than in other countries, or it may be that this economic growth performance has been accompanied by high inequality, thus diminishing the "quality" of growth. How is it that the country with the fastest growth in the region also has the highest inequality? Are the two facts related, and if so, what can be done to improve the pattern of future income growth across the social classes, and reduce its extreme inequality and the breadth and depth of its poverty? The first volume summarizes the overall conclusions for policy drawn from the seven background papers presented in the second volume, and other relevant research, as well as giving a historical account of the driving forces behind Brazilian growth since the 1960s.